PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT SYNTHESIS PROJECT LOGISTICS DI KOTA BATAM - Jibrail, Jumadi; hikmah, Hikmah (LPPM Universitas Putera Batam, 2019)
PT Synthesis Project Logistics was established on December 30, 2010 is a company engaged in the field of land transportation in Batam, specially for transportation for oil and gas companies. The formulation of the problem in this study is how the influence of motivation and work discipline on the performance of employees of PT Synthesis Project Logistics in Batam City. This study aims to determine the effect of motivation and work discipline on the performance of employees of PT Synthesis Project Logistics in Batam City. Thehypothesis in this study is that motivation and discipline affect the performance of employees of PT Synthesis Project Logistics in Batam City. This research method is quantitative. This research is in a convenient sampling. The sample used is 100 respondent system. The results of the motivation variable have a positive and significant effect on employee performance, with a value of 6.873> 1.98447 (t-table) and a significant value of 0.000 <0.05.For work discipline variables have a positive and significant effect on employee performance with a value of 3.887> 1.98447 (t-table) and a significant value of 0.000 <0.05.While simultaneously motivation and work discipline have a significant effect on employee performance with F count 50.311> F table 3.09, the significance value obtained is 0.000 <α 0, 05.